A Comparison of the Satisfaction among Customers of Medical Laboratory Services on External Quality Assessment Performed by Bureau of Laboratory Quality Standards and Other Public and Private Sectors - Tatsanakit, Amornrat; Piyarattanaworasakul, Suphawan (Journal of Health Science of Thailand, 2017)
The objective of this study was to analyze and compare the satisfaction of customers of laboratory services on external quality assessment performed by Bureau of Laboratory Quality Standards (BLQS) and other public and private sectors. It was conducted by sending questionnaire to responsible persons in customer organizations, and the study samples were 324 respondents. The analysis of the completed questionnaires revealed that the main service from the BLQS was clinical microscopy (86.12% of the BLQS customers), clinical immunology service at the public sector (39.09%), and clinical chemistry service at the private sector (45.89%). Comparison of satisfaction level using Likert’s scale and t-test of satisfaction level showed a significantly high level of satisfaction for the service quality of all three groups of service providers (p<0.05). Additionally, a test of average satisfaction with the services in the custom ers of different age ranges was performed using One-way ANOVA and least square difference (LSD) method, and it was found that the group of 51-60 years old was significantly satisfied with the service quality of the analysis at the BLQS when compared to the groups of 21-30, 30-40 and 41-50 years old (p<0.05). The most significant factor for customers’ dissatisfaction in the services performed BLQS and other public sector was the delay of assessment report submission. As for the private sector, the customers were not satisfied with the high service fees. In summary, the study of service comparison will be useful for the improvement of overall performance with the ambition to create customers’ trust, confidence, and satisfaction beyond their expectation.